24.4k views
2 votes
2. y = k2 - 13k +42​

User AndyHu
by
5.2k points

1 Answer

5 votes

For this case we must solve the following quadratic equation:


y = k ^ 2-13k + 42

With
y = 0 we have:


k ^ 2-13k + 42 = 0

The roots will be given by:


k = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Where:


a = 1\\b = -13\\c = 42

Substituting:


k = \frac {- (- 13) \pm \sqrt {(- 13) ^ 2-4 (1) (42)}} {2 (1)}\\k = \frac {13 \pm \sqrt {169-168}} {2}\\k = \frac {13 \pm \sqrt {1}} {2}\\k = \frac {13 \pm1} {2}

Thus, we have two roots:


k_ {1} = \frac {13 + 1} {2} = \frac {14} {2} = 7\\k_ {2} = \frac {13-1} {2} = \frac {12} {2} = 6

Answer:


k_ {1} = 7\\k_ {2} = 6

User Olorin
by
5.4k points